Governance Networks Analysis on Rice Distribution in Indonesia - Anika Widianaa; Chandra Wijayaa; Andreo Wahyudi Atmokoa (Kurdish Studies, 2024)
The rice distribution system in Indonesia suffers from complex problems involving numerous stakeholders with multiple perspectives. Departing from the situation, the researchers would like to analyze the problem of the national rice distribution by using the concept known as Governance Networks to attain an illustration of the good and strong rice distribution system in Indonesia. The distribution system has become a highly important element in rice problems throughout Indonesia. A strong distribution system will create a good market structure, including food and price stability. Therefore, the problems over the national rice distribution will be reviewed from the perspective of three aspects of Governance Networks, namely substantive complexity, strategic complexity, and institutional complexity. From the three aspects, the inter-factor relationship that has influenced the rice distribution in Indonesia can be identified, thus the driving factors for the performance and capacity growth in the rice distribution activities can be determined.